KEBUDAYAAN DALAM PANDANGAN HADIS - Caca handika (Diroyah : Jurnal Studi Ilmu Hadis, 2019)
This research is motivated by the existence of several bad habits that seem to have become a natural thing to do and have become a culture in the midst of society, even though that was clearly prohibited by the Prophet Muhammad in his hadith. There is also a habit that is recommended to be done even though not many people do it, especially Muslims. Even though the act was a habit of previous Muslims. So, this paper reveals the problem that exists in a Muslim especially regarding culture when viewed from the point of view of hadith.This research uses qualitative methods by conducting library studies or library research. The results of this study have no significant problems between the theory of sociology and anthropology with existing hadith texts on culture (both those which are prohibited and those recommended).However, more than that the author found that there was an idealization between people or communities who in fact were Muslims in carrying out Islamic sharia’s itself. Because it is evident from several cases revealed, the authors believe the majority of Muslims have known the law regarding it, both prohibited and recommended.Thus, the awareness of the people who are Muslim must be encouraged by the spirit of carrying out the Islamic Sharia. Because this is what can distinguish between Muslims who are religious and non-Muslim people who are practicing Islamic sharia’s.